Customer aggression and organizational turnover among service employees: The moderating role of distributive justice and organizational pride - Kashif, Muhammad; Zarkada, Anna K.; Thurasamy, Ramayah (My University, 2017)
Purpose: The episodes of customer rage with employees during service encounters are common and adversely affect the long-term commitment of employees with an organization. The service organizations, in an effort to control employee turnover, are striving hard but have failed. There are a wide variety of studies that address employee turnover but the research which encapsulates a combined effect of perceived justice and organizational pride to study exhaustion-turnover path are almost scant. The purpose of this paper is to explore the effects of customer aggression on the frontline food service managers’ emotional exhaustion and turnover intentions. The mitigating effects of perceived distributive justice and emotional organizational pride are also investigated. Design/methodology/approach: Survey data were collected from 250 frontline employees of global fast food chain outlets located in the city of Lahore, Pakistan. The data were analyzed using structural equation modeling by AMOS. Findings: The customer aggression is found to influence emotional exhaustion which in turn reduces job satisfaction and increases turnover intentions among frontline food service managers. The mitigating effects of distributive justice on the customer aggression to emotional exhaustion path and of emotional organizational pride on the job satisfaction to turnover intentions path are confirmed. Practical implications: The results reveal importance of maintaining a supportive and justice-oriented organizational culture. Rewarding frontliners, celebrating the organizational successes that build pride, and acknowledging the emotional burden misbehaving customers place on employees are identified as shields to guard against employee dissatisfaction and turnover. Originality/value: The turnover intentions resulting from the emotional exhaustion caused by customer aggression in the global fast food industry is studied for the first time. Furthermore, the inclusion of distributive justice and emotional organizational pride as cognitive and affective factors that reduce the effects of customer aggression on frontliners is unique to this study.
Keywords: Pakistan; Distributive justice; Emotional exhaustion; Fast food; Food service managers; Customer aggression; Emotional pride